Efeito dos probióticos Bacillus cereus var. Toyoi, Saccharomyces boulardii e Saccharomyces cerevisiae em ovinos infectados por nematódeos gastrintestinais - Corrêa, Tiago Gallina (2011)
The gastrointestinal parasitic infections caused by nematodes is one of most detrimental causes that impaired the sheep production, whereas the Haemonchus contortus have a role due to its pathogeny and prevalence. The methods of control are based on the use of anthelmintics, which can lead the resistence of nematodes. The objectives of these studies were to evaluate the effect of Bacillus cereus var. Toyoi (Bc), Saccharomyces boulardii (Sb) and S. cerevisiae (Sc) probiotics in lambs infected with gastrointestinal nematodes. In the Experiment 1; thirty two Texel breed lambs, aging 4 to 5 months, were randomized allocated into 4 experimental groups; Group 1 (n=8) that received Bc, 2) Group 2 (n=8), that received Sb, Group 3 (n=8); that received Sc. All groups treated with probiotics received the concentration of 1x106 CFU gr-1. The Group 4 did not receive any treatment. The animals were fed with probiotics individually once a Day during 56 days. Seven days after the beginning of the experiment, the animals were infected with H. contortus. Blood samples were collected weekly in order to evaluate hematological, biochemical and immunological parameters. The gene expression of pro-inflammatory cytokines were evaluated by RT PCR. On Day 49, after the infection, all animals were killed in order to recover the parasites and to evaluate histologically The abomasum. In Experiment 2, twenty Ideal breed lambs, with 4 to 5 months old, were fed with 1x106 UFC gr-1 of Sc and kept in two paddocks naturally contaminated with nematodes during one year. The worm burden, packed cell volume, gain of weigh and body condition score were measured. In the Experiment 1 the Sc group differ from the others groups (P < 0.05) on the worm burden and eosinophil counting on the abomasal mucosa. The levels of IL-4 showed an increase of 15 times in the animals treated with Sc and Sb. In the experiment 2, there was a significant reduction on the number of H. contortus recovered from abomasum (P < 0.01) compared with the control group. These results suggest that the treatment with Saccharomyces cerevisiae probiotic interferes with the immune response and reduces the worm burden of nematodes, being an alternative to improve the methods of control of nematodes.